Efficacy of Home Telemonitoring versus Conventional Follow-up: A Randomized Controlled Trial among Teenagers with Inflammatory Bowel Disease. (8th December 2017) - Heida, Anke; Dijkstra, Alie; Muller Kobold, Anneke; Rossen, John W; Kindermann, Angelika; Kokke, Freddy; de Meij, Tim; Norbruis, Obbe; Weersma, Rinse K; Wessels, Margreet; Hummel, Thalia; Escher, Johanna; et al.
Abstract: Background and Aims: Conventional follow-up of teenagers with inflammatory bowel diseases [IBD] is done during scheduled outpatient visits regardless of how well the patient feels. We designed a telemonitoring strategy for early recognition of flares and compared its efficacy with conventional follow-up. Methods: We used a multicentre randomized trial in patients aged 10–19 years with IBD in clinical remission at baseline. Participants assigned to telemonitoring received automated alerts to complete a symptom score and send a stool sample for measurement of calprotectin. This resulted in an individual prediction for flare with associated treatment advice and test interval. In conventional follow-up the health check interval was left to the physician's discretion. The primary endpoint was cumulative incidence of disease flares. Secondary endpoints were percentage of participants with a positive change in quality-of-life and cost-effectiveness of the intervention. Results: We included 170 participants [84 telemonitoring; 86 conventional follow-up]. At 52 weeks the mean number of face-to-face visits was significantly lower in the telemonitoring group compared to conventional follow-up [3.6 vs 4.3, p < 0.001]. The incidence of flares [33 vs 34%, p = 0.93] and the proportion of participants reporting positive change in quality-of-life [54 vs 44%, p = 0.27] were similar. Mean annual cost-saving was €89 and increased to €360 in those compliant to the protocol. Conclusions: Telemonitoring is as safe as conventional follow-up, and reduces outpatient visits and societal costs. The positive impact on quality-of-life was similar in the two groups. This strategy is attractive for teenagers and families, and health professionals may be interested in using it to keep teenagers who are well out of hospital and ease pressure on overstretched outpatient services. Trial registration: NTR3759 [Netherlands Trial Registry]